2018
DOI: 10.1142/s021849581850005x
|View full text |Cite
|
Sign up to set email alerts
|

“I Want to Be Like You!”: The Influence of Role Models on Entrepreneurial Intention

Abstract: Explaining individual’s entrepreneurial intention is a central element in entrepreneurship research. The purpose of this paper is to illustrate that role models have an indirect effect on students’ entrepreneurial intention. We draw on a sample of 266 individuals and apply structural equation modeling. Our results show that role models have a positive and significant influence on entrepreneurial intention via the antecedents described in the theory of planned behavior, the entrepreneurial event model, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 94 publications
5
31
0
1
Order By: Relevance
“…However, a significant negative relationship between the perception of SN and EI has been obtained (H3b), which means that the higher the consideration about entrepreneurial career among people around Latin American inhabitants, the lower the EI of these population (Guzman-Alfonso and Guzman-Cuevas, 2012). The negative influence of SN on EI, to some extent, is not surprising, since the findings on this relationship are not sufficiently consistent (Fellnhofer and Mueller, 2018;Krueger et al, 2000;Lopez and Alvarez, 2019;Mathews et al, 2001). In this sense, cultural components might be considered because they tend to vary in different cultures; therefore, the country's characteristics should be carefully analyzed.…”
Section: Entrepreneurial Intention In Latin Americamentioning
confidence: 92%
See 1 more Smart Citation
“…However, a significant negative relationship between the perception of SN and EI has been obtained (H3b), which means that the higher the consideration about entrepreneurial career among people around Latin American inhabitants, the lower the EI of these population (Guzman-Alfonso and Guzman-Cuevas, 2012). The negative influence of SN on EI, to some extent, is not surprising, since the findings on this relationship are not sufficiently consistent (Fellnhofer and Mueller, 2018;Krueger et al, 2000;Lopez and Alvarez, 2019;Mathews et al, 2001). In this sense, cultural components might be considered because they tend to vary in different cultures; therefore, the country's characteristics should be carefully analyzed.…”
Section: Entrepreneurial Intention In Latin Americamentioning
confidence: 92%
“…The SN dimension is undoubtedly the TPB construct that presents the most varied results regarding its impact as an EI antecedent. In this sense, previous studies interspersed results with some positive, others not significant and still others with sometimes even adverse effects on the SN-EI relationship (Fellnhofer and Mueller, 2018;Krueger et al, 2000;Lopez and Alvarez, 2019;Rodrigues et al, 2012;Souitaris et al, 2007). On the other hand, moderating effects are also tested in the sense of understanding how SNs are beneficial to understanding the process involved in becoming an entrepreneur, highlighting that the SN construct influences ATB and PBC (Liñ an and Chen, 2009;Liñ an and Santos, 2007;Tsai et al, 2016).…”
Section: Subjective Norms Affecting Attitude and Perceived Behavioral Controlmentioning
confidence: 99%
“…These other kinds of first-hand entrepreneurial experiences could possibly have an impact on diverse manifestations of entrepreneurial attitudes (cognition, affect and behavior), just as Athayde (2009) shows it for the Young Enterprise Company Program. Moreover, Fellnhofer and Mueller (2018) show that role models have an indirect effect on students’ entrepreneurial intentions. In the same way, meeting an entrepreneur could create affective conditions likely to impact young students’ entrepreneurial attitudes.…”
Section: Limitations and Future Researchmentioning
confidence: 92%
“…Additionally, Li, Wu, and Wu (2008) indicated that the expectancy of families and other key persons have significant influence on the career choices of university students. However, Lopez et al (2021) found a negative influence of subjective norms on intention, this indicated that the findings on this relationship are not sufficiently consistent (Fellnhofer & Mueller, 2018). Therefore, H3 was devised: H3.…”
Section: Subjective Norms On Entrepreneurial Intentionmentioning
confidence: 93%